Feto-maternal Outcomes in known Cirrhotic Pregnant Women - Farhana Anjum, Ambreen Amna Siddique, Kousar Fatima, Atteya Abbasi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the fetal and maternal outcomes among women presenting with diagnosis of liver cirrhosis. Material and Methods: This descriptive cross-sectional study was carried out at the Asian Hospital Hyderabad. The study duration was two years from November 2019 to October 2021. All the pregnant women having a diagnosis of advanced chronic liver disease, age more than 18 years of either parity or gestational age were included. All the patients were monitored until fetal birth and patients were assessed regarding maternal and fetal complications, including feto-maternal mortality. All the cases were managed by the senior gynecologists with minimum experience of 10 years with the collaboration of gastroenterologists as per indication. Pre-operative, per operative, and post postoperative treatment planes were discussed and done by the collaboration of senior gastroenterologist to decrease the procedure and post procedure complication. All the information was gathered via self-made study proforma. SPSS version 26 was used for the purpose of data analysis. Results: Total 19 patients were included with an average age of 33.15+5.42 years and average gestational age of 15.63+8.84 weeks. History of endoscopic band ligation was among 12(63.2%) of the cases. Normal vaginal delivery (NVD) was done in 36.8% women, C-section was performed in 26.3% women, missed abortion was medically terminated in 26.3% women, spontaneous complete abortion was in 05.3% and one twin pregnancy with both IUD fetuses was medically terminated. Antepartum hemorrhage (APH) was observed in 21.1% women, PPH was observed in 10.5% cases, PPROM was observed in 10.5% women, and 15.8% were admitted to ICU. Only 4 neonates were alive and out of these 2 were preterm, while 31.6% missed abortion was medically terminated, early neonatal death (ENND) occurred in 10.5% cases, still born were 05.2%, spontaneous complete abortion was 10.5% and 15.8% were IUD. Conclusion: It was concluded that the risk of adverse fetal and maternal outcomes was much higher in pregnancies affected by liver cirrhosis. Missed abortions found commonest. During advanced liver disease, patients were encouraged to avoid pregnancies by using the appropriate recommended contraceptive methods